Understanding the role of community resilience in addressing the Ebola virus disease epidemic in Liberia: a qualitative study (community resilience in Liberia) - O. Alonge; S. Sonkarlay; W. Gwaikolo; C. Fahim; J. L. Cooper; D. H. Peters (Taylor & Francis Group, 2019)
Background: There is an increasing recognition that community resilience plays a significant role in addressing health shocks like the Ebola virus disease (EVD) epidemic. However, the factors that constitute community resilience, and how these operate dynamically with other health system factors are less understood. Objective: This paper seeks to understand key factors that constitute community resilience and their role in responding to the EVD outbreak in Liberia. Methods: Key informant interviews were conducted between November 2017 and April 2018 with community representatives in Bomi, Margibi and Montserrado counties, and other national stakeholders involved in the EVD response in Liberia from 2014 to 2016. A national stakeholder meeting was conducted to verify and interpret information emerging from the interviews. Results: Factors that were critical for addressing the EVD epidemic in Liberia were identified as: strong leadership, tight bonds and sense of kinship at the community level; trusted communication channels; and trust among various health system stakeholders. These factors facilitated collective actions within communities and helped to direct response initiatives from other levels of the health system to the community. Foreign assistance was seen as crucial for recovery and revitalization of affected communities. However, such aid is often not targeted at addressing critical challenges in a sustainable way, especially when the assistance is highly restricted to specific activities, and those activities are determined without consultation with local actors and community groups. Conclusion: Efforts to systematically build responsible leadership and social capital at community level, including those that strengthen bonds in communities and trust across key actors in the health system, are needed to address health shocks like EVD outbreaks. Without building such capabilities in community resilience, it will be difficult to reap the expected gains from investments focusing on building physical capital and technical capabilities in health services and emergency preparedness.